Pengaruh Aset Pajak Tangguhan, Beban Pajak Tangguhan, Perencanaan Pajak, Asimetri Informasi, Dan Leverage Terhadap Earnings Management (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2014) - Sari, Esti Mustika, Drs. Muhammad Abdul Aris, M.Si (2016)
This study aims to provide empirical evidence of influence: deferred tax assets, deferred tax expense, tax planning, information asymmetry, and leverage to earnings management on the company's Manufacturing listed on the Indonesian Stock Exchange 2010-2014. Sample selection is done by purposive sampling method. This research was conducted using secondary data. The sample in this study were 19 companies listed on the Indonesian Stock Exchange (BEI) during the period 2010-2014. The analytical method used is descriptive statistics, hypothesis testing using logistic regression. The results of this study prove that five variables examined, ie deferred tax assets, deferred tax expense, tax planning, information asymmetry and leverage, leverage only variable that had a significance level of 0.033 <0.05 which indicates that the variable leverage effect on earnings management.